Singapore : Asian Solar Power Hub? - Eu, Gene Ang. (2008)
This dissertation studies the market penetration of solar power in Southeast Asian countries as compared to the rest of the world, identifies the key success factors for solar power marketing, and finally explores Singapore's potential to emerge as a regional hub for solar power activities in the Southeast Asian region.